2020
DOI: 10.1001/jamaneurol.2019.3924
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Prognostic Factors in C9orf72 Repeat Expansion Carriers

Abstract: The c9orf72 repeat expansion (c9 or c9orf72 RE) confers a survival disadvantage in amyotrophic lateral sclerosis (ALS); its effect on prognosis in frontotemporal dementia (FTD) remains uncertain. Data on prognostic factors in c9orf72 RE disorders could inform patient care, genetic counseling, and trial design. OBJECTIVE To examine prognostic factors in c9ALS, c9FTD, c9ALS-FTD, and atypical phenotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 68 publications
0
27
1
Order By: Relevance
“…In a population-based study by Chiò et al [6], genetic mutations did not modify the effect of sex on clinical phenotype, neither motor nor cognitive. Similarly, Glasmacher et al [109] did not find an association between sex and survival in C9orf72 repeat expansion carriers. With regard to evidence of potential sex-genetics interplay in C9orf72 repeat expansion (C9+) carriers, a recent meta-analysis on sex differences in genetic mutations in ALS and FTD showed that in women there has been a higher prevalence of expanded C9orf72-related ALS [104].…”
Section: Interplay Between Sex and Genetics In Als Pathogenesismentioning
confidence: 90%
See 1 more Smart Citation
“…In a population-based study by Chiò et al [6], genetic mutations did not modify the effect of sex on clinical phenotype, neither motor nor cognitive. Similarly, Glasmacher et al [109] did not find an association between sex and survival in C9orf72 repeat expansion carriers. With regard to evidence of potential sex-genetics interplay in C9orf72 repeat expansion (C9+) carriers, a recent meta-analysis on sex differences in genetic mutations in ALS and FTD showed that in women there has been a higher prevalence of expanded C9orf72-related ALS [104].…”
Section: Interplay Between Sex and Genetics In Als Pathogenesismentioning
confidence: 90%
“…In a population-based study by Chiò et al [6], genetic mutations did not modify the effect of sex on clinical phenotype, neither motor nor cognitive. Similarly, Glasmacher et al [109] did not find an association between sex and survival in C9orf72 repeat expansion carriers. gender-specific differences for age of onset in C9orf72-linked ALS: male subjects are more likely to express the disease at a younger age…”
Section: Interplay Between Sex and Genetics In Als Pathogenesismentioning
confidence: 90%
“…12 The association between age and survival is variably reported amongst FTLD subtypes. Older age appears to portend shorter survival from disease onset in bvFTD 13 and FTD-ALS 14 with variable reports in PSP 15,16,17 . A series of 100 patients with SD found no association between age and survival.…”
Section: Demographic Factorsmentioning
confidence: 95%
“…9 13 14 The initial presentation and disease course also vary widely (box 1, table 1); survival after symptom onset ranges from 2 months in rapidly progressive ALS to over 30 years in slowly progressive behavioural variant FTD (bvFTD). 14…”
Section: Epidemiology Of C9orf72 Repeat Expansionsmentioning
confidence: 99%
“…Other motor neuron diseases, including progressive muscular atrophy and primary lateral sclerosis, are rare in C9orf72 expansion carriers. 14…”
Section: Neurodegeneration Motor Neuron Diseasesmentioning
confidence: 99%